2015
DOI: 10.1080/19443994.2014.880159
|View full text |Cite
|
Sign up to set email alerts
|

Removal of hardness by electrodialysis using homogeneous and heterogeneous ion exchange membranes

Abstract: A B S T R A C TThe effect of membrane characteristics on removal of hardness ions from its dilute solutions using electrodialysis (ED) system by applying batch recirculation mode has been investigated. Two types of membrane pairs were used. Type I: Ionac MC3470 and MA3475 (Sybron Chem. Co.); Type II: Neosepta CMX and Neosepta AMX (Astom Corp.). These membranes have different ionic permselectivity, electrical resistance and thickness. In the first part of the study, the effects of the feed concentration, dilute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In this case, the issue of separation of mono- and divalent ions is becoming more and more important [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For example, membrane separation of lithium and magnesium or cobalt ions [ 43 , 44 , 45 , 46 , 47 ] and the removal of magnesium/calcium [ 48 , 49 , 50 , 51 ] have attracted increasing attention. On the contrary, membranes in fuel cells are usually in single ionic form (H + or OH − -form) and contact only with humidified gases or methanol.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the issue of separation of mono- and divalent ions is becoming more and more important [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For example, membrane separation of lithium and magnesium or cobalt ions [ 43 , 44 , 45 , 46 , 47 ] and the removal of magnesium/calcium [ 48 , 49 , 50 , 51 ] have attracted increasing attention. On the contrary, membranes in fuel cells are usually in single ionic form (H + or OH − -form) and contact only with humidified gases or methanol.…”
Section: Introductionmentioning
confidence: 99%
“…mobility of the transported ions divided by the sum of mobilities of all ions in solution), exchange capacities, and thickness of the cation-and anion-exchange membranes, along with applied voltage, feed flowrate, current density, operational mode, temperature, and time (El Midaoui et al 2002;Sirivedhin et al 2004). Karabacakoglu et al (2015) found 95-100 % Mg 2? removal and 93-98 % Ca 2?…”
Section: Electrodialysis (Ed)mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] The main advantage of electrodialysis is that it can be operated out at room temperature and atmospheric pressure. [31][32][33][34][35][36][37] Electrodialysis coupled with RO system can be most effective for high level of water purification.…”
Section: Introductionmentioning
confidence: 99%